Few figs for frugivores: Riparian fig trees in Zimbabwe may not be a dry season keystone resource. (8th August 2020) - Compton, Stephen G.; Greeff, Jaco M.
Abstract: Most plants flower and fruit at times of year when probabilities of pollination and seedling establishment are high. Fig trees ( Ficus spp.) are often considered as keystone resources for vertebrate frugivores, in part because of year‐round fig production. This unusual fruiting phenology results in the maintenance of fig wasp populations, but in seasonal environments this means fruiting occurs during periods when the chances of seedling establishment are low. Under these circumstances, selection is expected to favour any individuals that reduce or eliminate fruiting at these times. Here, we describe a large‐scale survey of the extent of dry season fruiting by three riparian Ficus species in Gonarezhou National Park, Zimbabwe. Few trees of two monoecious species, F. sycomorus and F. abutilifolia, had figs, and most crops of F. sycomorus were far smaller than the trees were capable of producing. Large stands of the dioecious F. capreifolia were present, but fig densities were low and no mature female (seed containing) figs were recorded. Even though fig trees may have been the only species bearing fruit, the consequences of the low investment in reproduction by the three Ficus species were clear—there were too few figs for a landscape‐scale keystone role. Résumé: La plupart des plantes fleurissent et fructifient à des moments de l'année où les probabilités de pollinisation et d'établissement des semis sont élevées. Les figuiers ( Ficus spp .) sont souvent considérés comme des ressources clés pour les frugivores vertébrés, en partie grâce à la production de figues toute l'année. Cette phénologie de fructification inhabituelle entraîne le maintien des populations de guêpes des figuiers, mais dans les environnements saisonniers, cela signifie que la fructification se produit pendant les périodes où les chances d'établissement des semis sont faibles. Dans ces circonstances, la sélection devrait favoriser tous les individus qui réduisent ou éliminent la fructification à ces moments. Nous décrivons ici une étude à grande échelle portant sur l'étendue de la fructification en saison sèche par trois espèces riveraines de Ficus dans le parc national de Gonarezhou, au Zimbabwe. Peu d'arbres de deux espèces monoïques, F. sycomorus et F. abutilifolia, avaient des figues et la plupart des fruit du F. sycomorus étaient beaucoup plus petits que ceux que les arbres étaient capables de produire. D'importants peuplements de F. capreifolia dioïque étaient présents, mais les densités de figues étaient faibles et aucune figue femelle mature (contenant des graines) n'a été enregistrée. Même si les figuiers étaient peut‐être la seule espèce à produire des fruits, les conséquences du faible investissement dans la reproduction par les trois espèces de Ficus étaient claires ‐ il y avait trop peu de figues pour qu'elles jouent un rôle clé à l'échelle du paysage.